Hegel en Lacan. Las trampas de lo imaginario y la función del lenguaje en la constitución del sujeto - Mariano de la Maza, Luis (Veritas, 2019)
This article exposes the presence of Hegel in the psychoanalytk theory of Lacan: first, the use that the latter makes of the dialectic of the master and the slave to illuminate the imaginary dimension of consciousness and desire, secondly, the reception of the Hegelian conception of language in connection with the symbolic function and the constitution of subjectivity, and finally the position of both with respect to the relationship between knowledge and truth. The three aspects contribute to illuminate the interpretation of the concept of subject in Lacan in light of the Hegelian influence.